# Identifying slope and y-intercept of a line?

I am understanding EVERYTHING up until now. I am just not understanding the part of rewriting the equation into slope intercept form. The problem is

2x=-4y+6

The part i am not understanding is that in the book it shows it as rewriting it as

-4y=2x-6 and then

y=-1/2x+3/2

okay so where did that -6 come from and why are the finishing results looking like fractions. I am basically not understanding the whole process of how that works.

I am not on here as a joke or to have someone just give me the answer. I take this very seriously so i WILL understand. If i wanted just the answer i would copy the whole thing out of the book. So please understand i am on here for complete understanding.

Thanks to all that help me.

### 5 Answers

- 1 decade agoFavorite Answer
Hey, no problem. No one learns algebra overnight, you know. XD

So you have 2x = -4y+6.

We want to bring y to the other side of the equation to isolate it. We use SPE [subtraction property of equality].

(4y) + 2x = -4y + (+4y) + 6,

4y + 2x = 6.

We use SPE again for 2x, to isolate 4y.

4y + 2x + (-2x) = 6 + (-2x),

4y = -2x + 6.

To isolate y, we divide both sides of the equation by 4.

4/4 y = -2/4 + 6/4.

We simplify the equation.

y = -1/2 + 3/2.

I hope you got my explanation. Haha. :)

Good luck with everything else! :D

Source(s): I took Algebra up in first and second year high school. XD- Login to reply the answers

- evalescoLv 41 decade ago
Okay, I think I can help with where the -6 came from. The important thing here is to look carefully at the minus signs.

2x = -4y + 6

In order to get y on its own, we need to first get -4y on the other side by adding -4y to both sides:

4y + 2x = 6

Now, we need to get 2x on the other side by subtracting it from both sides:

4y = 6 - 2x

Now, for some reason I'm not totally sure about, the book thinks it would be easier if the 2x were made positive instead of negative. To do this, we just multiply EVERYTHING by -1. This will give:

-4y = -6 + 2x OR -4y = 2x - 6

Multiplying everything by -1 changes every + sign to a - sign and vice versa.

Now, to remove the -4, we need to DIVIDE everything by -4.

-6 / -4 = -1.5 OR 3/2

2 / -4 = 0.5x OR 1/2

Therefore:

y = -1/2x + 3/2

I hope this helps. Good Luck!

- Login to reply the answers

- 1 decade ago
Basically you apply knowledge of algebraic equations and move "6" over to the other side of the equation, thus changing its 'sign' to equalise it:

+6 = -6

When you change the "-4y" to "4y", you have to change the other side in the same manner, which means it becomes "-2x +6".

Then it's simply a matter of dividing everything by 4 to get the singular y, which means:

2x / 4 = 1/2x

6/4 = 3/2

And so you get the final answer.

Source(s): Did this this year.- Login to reply the answers

- 1 decade ago
you subtract 6 from both sides. so it is 2x-6=-4y

then you divide everything by -4

so you get -1/2x+3/2=y

then put in slope intercept form

y=mx+b

y=-1/2x+3/2

Source(s): 6th grade algebra- Login to reply the answers

- How do you think about the answers? You can sign in to vote the answer.
- MavisLv 41 decade ago
its not minus 6 u r taking it away as u have done the opposite to before (adding it)

not sure bout the fractions bit.

sorry i cant explain it better

- Login to reply the answers